Some new evidence on human joint lubrication. Issue 4 (August 1975) - Unsworth, A; Dowson, D; Wright, V
Abstract : Theoretical consideration has been given to the use of pendulum machines which are used to examine the frictional properties of human joints by incorporating them as fulcra. As a result, a new type of pendulum machine has been built which incorporates the facility to apply sudden loads to the joint on starting the swinging motion, and also the ability to measure directly the frictional torque experienced by the joint. The results obtained from natural hip joints indicate the presence of squeeze film lubrication under conditions of sudden loading of a joint. In addition, a self-generated fluid film process was observed at low loads while at higher loads boundary lubrication appeared to be important. These results have been used to describe the lubrication regimens occurring in a normal activity such as walking. A single experiment carried out on a hip from a patient suffering from severe rheumatoid arthritis has also been reported and the frictional resistance was seen to be increased fifteenfold compared to a normal hip.